ANALYSIS OF KNOWLEDGE AND ATTITUDES ON PPE COMPLIENTE AMONG PRODUCTION WORKERS AT PT.X - Dewi Kusuma Febrianti; Puspita Puji Rahayu (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
This study aims to analyze the relationship between knowledge and attitudes and compliance with the use of Personal Protective Equipment (PPE) among production workers in the food industry in Semarang. The study employed a quantitative approach with a cross-sectional design involving production workers as respondents. Data were collected through questionnaires to measure levels of knowledge and attitudes, as well as direct observation to assess compliance with PPE usage. Data analysis was conducted using descriptive and bivariate methods to identify relationships between variables. The results showed that there is a relationship between knowledge and attitudes and compliance with PPE usage. Workers with a higher level of knowledge and positive attitudes tend to be more compliant in using PPE compared to those with lower knowledge and negative attitudes. However, compliance is not only influenced by individual factors but also by workplace environmental factors such as supervision, safety culture, and the comfort of PPE use. These findings emphasize that improving compliance requires a comprehensive and integrative approach. The conclusion of this study is that knowledge and attitudes are important determinants in shaping compliance behavior in PPE usage; however, their effectiveness is strongly influenced by workplace support. Therefore, strategies to improve occupational safety should include continuous education, strengthened supervision, and the development of a safety culture within the industrial environment.